Use of Quantitative PCR To Measure Density of Borrelia burgdorferi in the Midgut and Salivary Glands of Feeding Tick Vectors - Piesman, Joseph (American Society for Microbiology, 2001)
Quantitative real-time PCR was used to assay spirochetes in feeding ticks. Spirochetes in tick midguts increased sixfold, from 998 per tick before attachment to 5,884 at 48 h of attachment. Spirochetes in tick salivary glands increased >17-fold, from 1.2 per salivary gland pair before feeding to 20.8 at 72 h postattachment. The period of the most rapid increase in the number of spirochetes in the salivary glands occurred from 48 to 60 h postattachment; this time period coincides with the maximal increase in transmission risk during nymphal tick feeding.